Correlation Between TNF- α and Degree of Gastritis - Ricky Rivalino Sitepu; Darmadi Darmadi; Gontar Alamsyah Siregar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: TNF- α is a cytokine that plays an active role in the pathogenesis of gastritis. The correlation of TNF-α levels in the gastric mucosa with the severity of gastritis has long been known. However, few studies have assessed TNF-α levels in serum of gastritis patients. This study aims to evaluate correlation between serum TNF-α level with the degree of gastritis based on histopathology.Method: A cross sectional study on eighty gastritis patients that fulfilled the inclusion criteria underwent serum TNF-α examination, endoscopy, and biopsy. Rapid urease test was used for diagnosis of H. pylori infection. The severity of gastritis based on lymphocyte infiltration, neutrophil infiltration, atrophy, and intestinal metaplasia according to Updated Sydney System. Univariate and bivariate analysis (Chi-square, fisher's exact, spearman correlation, and independent T-test) were done using SPSS version 22.Results: There were 41.25% patients infected with Helicobacter pylori. Serum TNF-α levels in the infected group were significantly higher compared to negative H. pylori (p 0.05). There was significant positive correlation between serum TNF-α levels and degree of gastritis based on lymphocyte infiltration (r = 0.333; p = 0.003).Conclusion: There was a significant positive correlation between serum TNF-α level with the severity of gastritis based on lymphocyte infiltration.